The contribution of sectoral output towards Malaysia economic growth / Baidahtul Edrah Ismail - Ismail, Baidahtul Edrah (2014)
Malaysia have recently fluctuated data of economic growth where GDP growth uncertainty trend because depend on contribution by sector output. Thus, this study examines the contribution of sectoral output towards Malaysia economic growth by using time series data from year 1982 until 2012. There are three economic sectors that will be analysed, which are agricultural sector, manufacturing sector and service sector. Ordinary Least cost (OLS) is used in this study and it showed that the time series data are significant except agriculture. Then, correlation analysis indicated that agriculture sector, manufacturing sector and service sector had positive relationship with dependent variables to independent variables and the independent variables with other independent variables. In addition, results of OLS showed that manufacturing sector generated the highest contribution to Malaysia's economic growth.